Psychology of learning: an Islamic theory - Alias, Alizi; Abdul Majid, Hariyati Shahrima (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
The objective of this article is to provide an Islamic perspective on the psychology of learning. This is a theoretical study based on reviews of secondary sources on Islamic and conventional psychology. It analyzes four conventional theories namely classical conditioning theory, operant conditioning theory, observational learning theory, and insight learning theory. It is argued that the fundamental elements of these theories go against the Islamic belief system, but certain other elements conform to Islamic beliefs. Referring to ibn Sina and al-Ghazali‟s treatment of many aspects of these theories and reflecting on the practices of the Companions during the time of Prophet Muhammad (SAW), the article argues that the fundamental difference between the conventional theories of psychology of learning and the Islamic theory of psychology of learning is the factor of human soul. In conventional theories, the soul as a factor is completely discounted, while in Islamic theory it is considered to be central.